If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 3y = 12 Solving 15x + 3y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 15x + 3y + -3y = 12 + -3y Combine like terms: 3y + -3y = 0 15x + 0 = 12 + -3y 15x = 12 + -3y Divide each side by '15'. x = 0.8 + -0.2y Simplifying x = 0.8 + -0.2y
| 2x+5x+34*6/46=8 | | 2x+5xx=990 | | x^2=11 | | 2x+5-(2573)-257xxx=2 | | 2x+x^2=12 | | 2x+5-(-4)=4x | | 7-10x^2=1 | | 2x+72=0 | | 7x+7(x-60)=5180 | | x+(-12)=4 | | .5x+6=.3x | | .5+6=.3x | | 200-7x=110-2x | | 4(1+2x)+5=(x+6) | | -(5x^4-36x^2)*0.25=0 | | 10z+8z+2=12z+9z+5 | | -5x^4+36x^2=0 | | 5x^2-5x-2=0 | | x^3-12x^2+36x=0 | | 12x+108=96 | | x^2+10x+21= | | x+18+4x=-11-4x-16 | | .333x+8=x+10 | | x^2-8x-16=23 | | .5x+8=x+10 | | 3x+51= | | x^2=500 | | 43+2x=32 | | 3(3)+5(4)=29 | | 6x-43=3x-10 | | 93+4=[17-(2+3)] | | 4x-7=3.5+x |